Between two worlds George Tyrrell's relationship to the thought of Matthew Arnold - Sagovsky, Nicholas 1947- (Cambridge University Press, 1983)
Tyrrell and Arnold take their place in a peculiarly English theological tradition. Appreciation of this tradition is of the first importance in understanding the background to contemporary Anglicanism and contemporary Catholicism. More than that, it offers a way of bridging the gulf between the world that to Tyrrell and Arnold was dead or dying and the world of the late twentieth century with all the questions that they began to perceive - two prophetic individuals unable to live with the Church of their day and unable to find the Church of the future